2019
DOI: 10.1002/jat.3800
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and proinflammatory responses induced by ZnO nanoparticles in in vitro intestinal barrier

Abstract: ZnO nanoparticles (NPs) are widely used nowadays, thus the gastrointestinal exposure to ZnO NPs is likely to be relevant and the effects on the intestinal barrier should be investigated. Polarized Caco-2 cells were exposed from the apical (Ap) and basolateral (Bl) compartments to increasing concentrations (0, 10, 50 and 100 μg/mL) of sonochemical (sono) and commercial ZnO NPs. The transepithelial electrical resistance (TEER), cell viability, proinflammatory cytokine release and presence of protein oxidative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This balance, together with the over-expression of TJ genes, likely contributes to prevent barrier damage and integrity loss. Our data are in line with the work of Colombo and co-workers, reporting that commercial ZnO nanoparticles increase IL-6 and IL-8 production in Caco-2 barrier model, maintaining barrier integrity [ 127 ]. Similarly, polyvinyl chloride particles have been reported to induce IL-1β secretion without altering Caco-2/HT29-MTX/THP1 barrier integrity and viability [ 128 ].…”
Section: Discussionsupporting
confidence: 92%
“…This balance, together with the over-expression of TJ genes, likely contributes to prevent barrier damage and integrity loss. Our data are in line with the work of Colombo and co-workers, reporting that commercial ZnO nanoparticles increase IL-6 and IL-8 production in Caco-2 barrier model, maintaining barrier integrity [ 127 ]. Similarly, polyvinyl chloride particles have been reported to induce IL-1β secretion without altering Caco-2/HT29-MTX/THP1 barrier integrity and viability [ 128 ].…”
Section: Discussionsupporting
confidence: 92%
“…Low toxicity and low inflammatory profile of novel NMs are essential for their safety. The concentrations of ZnO NPs generally used in the literature are within the range of 25 to 100 µg/mL, and the effects reported in vitro almost suggest safety for this NP [41]. The same is reported for toxicity of SiO 2 NPs that occurs to be dependent on dose, size, time, and temperature in addition to on the tissue-specificity.…”
Section: Discussionmentioning
confidence: 58%
“…Organic and inorganic nanoparticles (NPs) Adult Stem Cells (ASCs) [50] Iron oxide nanoparticles (IONPs) Primary cultures of brain cells [51] Various types of nanoparticles Cardiac stem cells [52] Gold nanoparticles breast cancer SK-BR-3 cells [53] titanium dioxide (TiO 2 ) nanoparticles A549 cells [54] ZnO nanoparticles Caco-2 cells [41] biosynthesized silver nanoparticles (ScAgNPs) THP-1 cells [55] Cerium dioxide nanoparticles (CeO 2 NPs) A549 cells and THP-1 cells (co-culture) [56] Silver (Ag), titanium dioxide (TiO 2 ), and zinc oxide (ZnO) nanoparticles THP-1 cells [57] Tantalum (Ta) and Titanium (TiO 2 ) NPs THP-1 cells [58] Silver nanoparticle (AgNP) THP-1 cells [59] Polystyrene NP (PLNP) A549 cells and THP-1 cells [60] Amino-functionalized silicon nanoparticle (NH2SiNP) MC3T3-E1 and PC12 cells and Danio rerio (embryos) [61] Iron nanoparticles Xenopus laevis (embryos) [62] Titanium dioxide NPs (n-TiO(2)) Danio rerio (embryos) [63] Silicon dioxide nanoparticles (nano-SiO(2)) Danio rerio (embryos) [64] Ag nanoparticles (NPs), CuO NPs, silica NPs, polymeric NPs, quantum dots Danio rerio (embryos) [65] Zirconia oxide nanoparticles (ZrO 2 NPs) Danio rerio (embryos) [66] Polyethylene glycol (PEG)-modified SiNPs Danio rerio (embryos) [67] Silver (AgNPs), copper nanoparticles (CuNPs) Danio rerio (embryos) [68] Silver nanoparticles (Ag NPs) of three different sizes (10, 40, and 100 nm) Danio rerio (embryos) [69] Hollow selenium nanoparticles (hSeNPs) Danio rerio (embryos) [70] Copper oxide nanoparticles (CuO NPs) Danio rerio (embryos) [71] Synthetic silver nanoparticles (AgNPs) Danio rerio (embryos) [72] Fluorescently-labeled SiO 2 NPs of 25 and 115 nm Danio rerio (embryos) [73] Citrate-functionalized IONPs (γ-Fe 2 O 3 ) NPs Danio rerio (embryos) [74] Silver nanoparticles (AgNPs) Danio rerio (embryos) [48] Metal nanoparticles (Au, Ag, Cu), and metal oxide nanoparticles (TiO 2 , Al 2 O 3 , CuO, NiO, ZnO) Danio rerio (embryos) [75] Zinc oxide nanoparticles (ZnONPs) Danio rerio (embryos) [76] Sliver nanop...…”
Section: Nanoparticles Biological Materials Referencementioning
confidence: 99%
“…Some studies identified negative biological consequences, for example an increased intestinal inflammation, decreased cell viability and depolarization of mitochondrial membranes, induced by the ZnO NP treatment [ 11 , 12 ]. Others showed rather inconclusive results that could not demonstrate ZnO NP toxicity in some assays, for instance an unmodified monolayer permeability but a disrupted brush border membrane [ 13 17 ], or concluded the innocuousness of a ZnO NP exposure [ 18 23 ]. The toxicity seems to depend on the used cell model, among other factors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%